Facet evolution of Al0.5Ga0.5As/GaAs multilayers grown on mesa-patterned GaAs substrate - Kim, HJ; Park, YK; Kim, SI; Kim, EK; Kim, TW (JAPAN J APPLIED PHYSICS, 1999)
Facet evolution of (511)A of Al0.5Ga0.5As/GaAs multilayers grown on a mesa-patterned GaAs substrate by metalorganic chemical vapor deposition has been investigated. The time development equation of the growth morphology together with the bond density model was introduced to analyze the facet evolution. The facets at the concave surface on the mesa-patterned GaAs substrate during the growth process were evolved toward the growth surface with the highest growth rate. The facets having the highest growth rate were analyzed as a function of the surface migration length. The calculated results show that the highest growth rate in the surface plane of (511)A occurred at the concave surface on a mesa-patterned GaAs substrate with a surface migration length of larger than 1.5 mu m.
Keywords: CHEMICAL-VAPOR-DEPOSITION; QUANTUM-WIRE STRUCTURES; CRYSTALLOGRAPHIC ORIENTATION; EPITAXIAL-GROWTH; CBR4; DEPENDENCE; MOCVD; CCL4